Handbook of play therapy - O'Connor, Kevin J.; Schaefer, Charles E.; Braverman, Lisa D. (John Wiley & Sons, Inc., 2016)
"Handbook of Play Therapy is the one-stop resource for play therapists with coverage of all major aspects written by experts in the field. This edition consolidates the coverage of both previous volumes into one book, updated to reflect the newest findings and practices of the field"--Provided by publisher.